PERTIMBANGAN HAKIM DALAM PENJATUHAN PUTUSAN PIDANA PENJARA MELEBIHI KETENTUAN PIDANA MAKSIMUM: Risca Agustin - admin, admin; Hariz Hamdallah, Muhammad Andika (Fakultas Hukum Universitas Islam Jakarta, 2017)
In each judge's decision, it should exist the consideration as the reason from the decision taken. In executing the decision, it should be based on the applicable legislation rules. The supreme court in rate an appeal can cancel a verdict or determination of the courts who located within the judicial underneath by the reasons, namely: not authorised or going beyond the authority, any apply or breaking the law and neglectful meeting requirements required by the law and the rule threatening omission of that decision which is cancelled. The method of this research is a yuridicial normative. This research attempts to know whether the judge consideration in a verdict MA No. 52 K/ Pid.Sus/ 2013 about corruption exceeding the maximum imprisonment, to find out the judicial decision that exceeds criminal maximum in accordance with the regulations. The result in this study is the decisions of the supreme court No. 52 K/ Pid.Sis/ 2013 in which the judge consideration supreme court is the decision on the high court in line with the rule of legislation. Whereas, supreme court judges rejected an appeal that proposed by Gayus H.P Tambunan. the decisions are inflected by a judge that should be based on the rules that has been set up in legislation. The length of an imprisonment that must be lived for 30 years in which it was not in accordance with legislative's regulation article 12 the book of the act of criminal law governing the length of an imprisonment during a certain time certainly may not exceed twenty years.